WHY THE AUTOMOTIVE INDUSTRY IS THE RIGHT CHOICE FOR INVESTMENT - Amelia, Novi; Andriani, Wery; Primadyan, Maretha (Unand Press, 2025)
The automotive industry is one of the industries attracting international investors. In Indonesia, the automotive industry serves as a crucial foundation for the development of the manufacturing sector. Financial analysis is needed to analyze company prospects and performance using figures available in financial reports. This analysis is necessary to assess whether company policies are appropriate, resulting in good performance and a return on investment for investors and creditors. This study attempts to assess whether the automotive industry is a suitable investment option. The data used in the analysis are obtained from the financial statements of automotive companies listed on the Indonesia Stock Exchange. The observation period is 2019-2023. The analysis uses solvency ratios, profitability ratios, market ratios, and dividend policies. The results of the analysis show fluctuating results for the five automotive companies analyzed. Over the past year, observations have shown that automotive companies have fluctuated in performance but are showing signs of improving. Investors are advised to choose companies with sufficient stability if they wish to continue investing in this industry